Pengaruh Berbagai Tingkat Penggunaan Ampas Ganyong (Canna edulis Kerr) dalam Ransum terhadap Fermentabilitas dan Kecernaan (In Vitro) - A. R. Widiyanti; E. Cardi; U. H. Tanuwiria; A. R. Tarmidi; I. Hernaman (Jurnal Peternakan, 2020)
Canna waste is the processing waste of canna tubers into flour. This feed ingredient has potential as ruminant feed. The research aims to evaluate the use of canna waste in rations in vitro. The study used a completely randomized design with 4 treatments and 5 replications. The treatments were rations containing 0% (R0), 10% (R1), 20% (R2) and 30% (R3) canna waste. The resulting data were analyzed by Duncan’s test. The use of canna waste did not have a significant effect on the production of N-NH3, but caused a decrease (P <0.05) on volatile fatty acids, dry matter digestibility and organic matter digestibility. Rations containing more than 20% of canna’s waste cause volatile fatty acids below the normal range and digestibility of dry matter <50%. The relationship between volatile fatty acids with dry matter digestibility and organic matter digestibility shows a linear line equation, namely: y = 0.1459x + 34.7779 with R2 = 0.8278, r = 0.9098 and y = 0.1159x + 40.794 with R2 = 0.7978, r = 0.8931. The results of the study concluded that the use of canna waste in the ration was a maximum of 10%.